2011
DOI: 10.1007/s00705-011-0966-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the six internal genes of H5N1 equine influenza A virus

Abstract: Phylogenetic and evolutionary patterns of the six internal genes of an equine H5N1 influenza A virus isolated in Egypt on 2009 were analyzed using direct sequencing. All of the internal genes of the equine H5N1 strain showed a genetic pattern potentially related to Eurasian lineages. Variable dendrogram topologies revealed an absence of reassortment in the equine strain while confirming its close relatedness to other Egyptian H5N1 strains from human and avian species. The equine strain is characterized by a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Key changes in this polymerase protein increase virus replication in mammals (Gao et al , 2009; Yamada et al , 2010). Our data show that this mutation is still common in Egyptian viruses, as reported previously (Abdel-Moneim et al , 2011; Kayali et al , 2011b), and was found in all viruses of the new cluster.…”
Section: Discussionsupporting
confidence: 88%
“…Key changes in this polymerase protein increase virus replication in mammals (Gao et al , 2009; Yamada et al , 2010). Our data show that this mutation is still common in Egyptian viruses, as reported previously (Abdel-Moneim et al , 2011; Kayali et al , 2011b), and was found in all viruses of the new cluster.…”
Section: Discussionsupporting
confidence: 88%
“…Still needing an answer is the question of whether such peculiar amino acids play a role in the virulence and/or transmission of H5N1 virus to equine or not. 128 Other animals…”
Section: H5n1mentioning
confidence: 99%
“…Several amino acid sites (AASs) in IAV RNPs were reported to affect IAV RNP activity or were associated with IAV host adaptation [15][31]. In total, 99 AASs (25 in the PA protein, 16 in the PB1 protein, 31 in the PB2 protein and 27 in the NP protein) from these reports were mapped to 185 SLiMs (42 in the PA protein, 35 in the PB1 protein, 67 in the PB2 protein and 41 in the NP protein) identified in this study (Table 2– 5).…”
Section: Resultsmentioning
confidence: 99%